Fostering intercultural communicative competence through reading authentic literary texts in an advanced colombian efl classroom: a constructivist perspective (2012)
This article describes an action research experience carried out in an advanced English as a foreign language classroom of the language program at a university in Bogotá, Colombia, in 2010. The study proposes the inclusion of authentic literary texts in the English as a foreign language classroom through the implementation of four constructivist approaches as a means to develop intercultural communicative competence. Data were collected to show how those approaches engaged learners to read authentic literary short stories, to negotiate meaning, and to develop intercultural competence. It demonstrates that integrating language and literature in English as a foreign language not only constitutes a communicative reading practice, but the opportunity to construct cultural knowledge through social interaction. Este artículo describe una experiencia de investigación acción llevada a cabo en una clase de inglés avanzado del programa de lenguas de una universidad colombiana en Bogotá, en el año 2010. El estudio propone la inclusión de textos literarios auténticos en el contexto de inglés como lengua extranjera mediante la implementación de cuatro enfoques constructivistas como recurso para desarrollar la competencia comunicativa intercultural. Los datos recolectados demuestran cómo tales enfoques contribuyeron a que los estudiantes leyeran cuentos literarios auténticos, negociaran significado y desarrollaran su competencia intercultural. La integración del lenguaje y la literatura no solamente constituye una práctica de lectura comunicativa, sino la oportunidad de construir conocimiento cultural a través de la interacción social.